Deletion of the scavenger receptor Scarb1 in osteoblast progenitors and myeloid cells does not affect bone mass - Michela Palmieri; Teenamol E. Joseph; Horacio Gomez-Acevedo; Ha-Neui Kim; Stavros C. Manolagas; Charles A. O’Brien; Elena Ambrogini (PLoS ONE, 2025)
The scavenger receptor class B member 1 (SCARB1), encoded by Scarb1 , is a cell surface receptor for high density lipoproteins, low density lipoproteins (LDL), oxidized LDL (OxLDL), and phosphocholine-containing oxidized phospholipids (PC-OxPLs). Scarb1 is expressed in multiple cell types, including osteoblasts and macrophages. PC-OxPLs, present on OxLDL and apoptotic cells, adversely affect bone metabolism. Overexpression of E06 IgM – a natural antibody that recognizes PC-OxPLs– increases cancellous and cortical bone at 6 months of age in both sexes and protects against age- and high fat diet- induced bone loss, by increasing bone formation. We have reported that SCARB1 is the most abundant scavenger receptor for OxPLs in osteoblastic cells, and osteoblasts derived from Scarb1 knockout mice ( Scarb1 KO) are protected from the pro-apoptotic and anti-differentiating effects of OxLDL. Skeletal analysis of Scarb1 KO mice produced contradictory results, with some studies reporting elevated bone mass and others reporting low bone mass. To clarify if Scarb1 mediates the negative effects of PC-OxPLs in bone, we deleted it in osteoblast lineage cells using Osx1-Cre transgenic mice. Bone mineral density (BMD) measurements and micro-CT analysis of cancellous and cortical bone at 6 months of age did not reveal any differences between Scarb1 ΔOSX-l mice and their wild-type (WT), Osx1-Cre, or Scarb1 fl/fl littermate controls. We then investigated whether PC-OxPLs could exert their anti-osteogenic effects via activation of SCARB1 in myeloid cells by deleting Scarb1 in LysM-Cre expressing cells. BMD measurements and micro-CT analysis at 6 months of age did not show any differences between Scarb1 ΔLysM mice and their WT, LysM-Cre, or Scarb1 fl/fl controls. Based on this evidence, we conclude that the adverse skeletal effects of PC-OxPLs in adult mice are not mediated by Scarb1 expressed in osteoblast lineage cells or myeloid cells.